Parametric Investigation on the Response of High-Density Polyethylene Pipes to Eccentric Loading - Elmrom, Tawfeg; Alfergani, Muna; Bowman, Elisabeth (International Journal of Engineering Research, 2025)
The durability of water distribution net- works partly relies on the ability of utility pipes to resist surface loading. In this paper, a parametric study is undertaken to investigate the response of high-density polyethylene (HDPE) pipes to eccentric loading. The results taken from a centrifuge model are used to evaluate the ability of a computational model to predict the bending moment distribution along the pipe. Following this validation process, the behaviour of HDPE pipes at a range of burial depths, and loading eccentricities is investigated further using the computational model. The results of this analysis are used to evaluate the High- way Agency guidelines for HDPE pipe burial depths, and they are found to be satisfactory, as they prevent exposure to the significantly higher bending moments experienced at shallow depths.